An Uncommon Cause of Recurrent Dysphagia and Chest Pain in an Adolescent Boy - Craveiro Costa, R (2024)
An 11-year-old boy was brought to the emergency department with a week-long history of widespread pain in his upper abdomen that worsened with deep breathing and eating, sialorrhea, food impaction sensation, and a recent fever. Ten months prior, he had similar symptoms and was diagnosed with a pharyngeal phlegmon. He was treated with antibiotics and dexamethasone. In the current episode, he presented with mild elevation of inflammatory markers, a slight deviation of the trachea on chest X-ray, and a tubular esophageal duplication was identified on a thoracic CT, with its opening observed during the endoscopic study. The patient was admitted for further treatment with fluids, analgesia, and antibiotics, and showed improvement over the next seven days with no significant incidents. Esophageal duplications are a rare congenital anomaly and their exact cause is unknown. Typically found in the posterior mediastinum and lower esophagus, they can cause symptoms such as pain, dysphagia, regurgitation, and malnutrition. Surgical or endoscopic resection can be a treatment option for these malformations.